PENGARUH HARD SKILL, SOFT SKILL DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN: (Studi Pada Tok The Athlete’s Foot SUN Plaza dan Delipark Medan) - Rani Indah Putri; Kartini Harahap (Transpublika Publisher, 2023)
In the current era of globalization, every company is required to be prepared to face various types of competition in the business world and must be able to enhance employee performance. This research aims to determine whether the influence of Hard Skill, Soft Skill, and Work Experience of each employee is greater compared to the influence of the brand in influencing consumers' purchasing decisions for a product. This study employs a quantitative approach with an associative method. The population for this research consists of 36 respondents, using a saturated sampling technique. Data collection is carried out through interviews and distributing questionnaires. The data analysis methods include validity test, reliability test, classical assumption test, multiple linear analysis, partial test, and determination test. The findings indicate that Hard Skill, Soft Skill, and Work Experience variables have a positive and significant impact on employee performance. These variables also have a simultaneous influence on employee performance, with an R-value of 0.705, indicating that these factors account for 70.5% of the variance in employee performance, signifying a strong influence. The Adjusted R Square value is 45%, implying that the remaining 55% is influenced by other variables not explained in this study.